Bergamot Essential Oil (Citrus bergamia) sebagai Terapi Alternatif Lanjutan untuk Komplikasi Kesehatan yang disebabkan oleh Internet Gaming Disorder (IGD) - Intan Lestari (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2020)
Activities that are liked by everyone to fill the spare time, especially boys, is playing games online or video-games. The increased duration of playing games can be addictive when playing games and restlessness if he do not play games. If this things continues it can develop into Internet Gaming Disorder (IGD) or gaming disorder. In 2018, International Classification of Diseases (ICD) released an 11th revision and stated that “gaming disorder” was officially declared as a disease. IGD can also potentially cause depression, social difficulties, ADHD and substance abuse. The fruit of the bergamot plant (Citrus bergamia) can be used for bergamot essential oil (BEO) by squeezing and cold pressing the fruit skin. Bergamot essential oil is widely used as aromatherapy to improve mood and symptoms of stress disorders. The aromatic materials will stimulate the autonomic nervous system so the receptors will receive BEO containing linalyl acetate and linalool. The odor will be delivered to the limbic system so that it can improve mood and trigger the release of hormones serotonin and endorphins